The chief justiceship of John Marshall, 1801-1835 - Johnson, Herbert Alan (University of South Carolina Press, 1997)
Perhaps no individual has exerted a more profound influence on the United States Supreme Court or on the federal Constitution than Chief Justice John Marshall. In this history of the high court during the critical years from 1801 to 1835, Herbert A. Johnson offers a comprehensive portrait of the court's activities and accomplishments under Marshall's leadership. Johnson demonstrates that in addition to staving off political attacks from the Jeffersonian and Jacksonian political parties, the Marshall Court established the supremacy of the federal government in areas of national concern, enunciated the commerce and contract clauses as critical foundations for economic development, and definitively shaped the structure of federalism before the Civil War.
Keywords: Marshall, John, -- 1755-1835.; United States. -- Supreme Court -- Biography.; États-Unis. -- Supreme Court -- Biographies.; Marshall, John, -- 1755-1835; United States. -- Supreme Court; United States. -- Supreme Court -- History.; Marshall, John (Politiker); Judges -- United States -- Biography.; Juges -- États-Unis -- Biographies.; LAW -- Government -- Federal.; POLITICAL SCIENCE -- Government -- Judicial Branch.; LAW -- Legal Services.; LAW -- Civil Procedure.; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges.; Judges; United States; Supreme Court (VS); Law - U.S.; Law, Politics & Government.; Law - U.S. - General.; Biographies; Biographies.